Decoy Receptor 3 Inhibits Monosodium Urate-Induced NLRP3 Inflammasome Activation via Reduction of Reactive Oxygen Species Production and Lysosomal Rupture - Pan, Yi-Gen; Huang, Ming-Ting; Sekar, Ponarulselvam; Huang, Duen-Yi; Lin, Wan-Wan; Hsieh, Shie-Liang (Frontiers in Immunology, 2021)
Gout is a common inflammatory arthritis caused by the deposition of monosodium urate (MSU) crystals in the joints. This activates the macrophages into a proinflammatory state by inducing NLRP3-dependent interleukin-1β (IL-1β) secretion, resulting in neutrophil recruitment. Soluble decoy receptor 3 (DcR3) is an immune modulator and can exert biological functions via decoy and non-decoy actions. Previously, we showed that DcR3 suppresses lipopolysaccharides (LPS)- and virus-induced inflammatory responses in the macrophages and promotes the macrophages into the M2 phenotype. In this study, we clarified the actions of DcR3 and its non-decoy action motif heparin sulfate proteoglycan (HSPG) binding domain (HBD) in the MSU crystal-induced NLRP3 inflammasome activation in the macrophages and in mice. In bone marrow-derived macrophages, THP-1 and U937 cells, we found that the MSU crystal-induced secretion of IL-1β and activation of NLRP3 were suppressed by both DcR3.Fc and HBD.Fc. The suppression of the MSU-induced NLRP3 inflammasome activation is accompanied by the inhibition of lysosomal rupture, mitochondrial production of the reactive oxygen species (ROS), expression of cathepsins, and activity of cathepsin B, without affecting the crystal uptake and the expression of NLRP3 or pro-IL-1β. In the air pouch mice model of gout, MSU induced less amounts of IL-1β and chemokines secretion, an increased M2/M1 macrophage ratio, and a reduction of neutrophil recruitment in DcR3-transgenic mice, which expresses DcR3 in myeloid cells. Similarly, the mice intravenously treated with DcR3.Fc or HBD.Fc displayed less inflammation response. These findings indicate that HBD of DcR3 can reduce MSU crystal-induced NLRP3 inflammasome activation via modulation of mitochondrial and lysosomal functions. Therefore, we, for the first time, demonstrate a new therapeutic potential of DcR3 for the treatment of gout.